Updates in chronic obstructive pulmonary disease (COPD) - Usmani, Omar S. (Henry Stewart Talks, 2017)
Clinical characteristics and pathophysiology of COPD, Pathophysiology of COPD, Assessing the lungs in COPD, COPD disease classification, Therapeutic management of COPD